HANDLING UNEMPLOYMENT IN INDONESIA - Nurrahman, Agung (Program Studi Studi Kependudukan dan Pencatatan Sipil, 2024)
This study aims to identify studies that reflect the trend of a series of publications related to unemployment issues in Indonesia and describe them visually. This research method uses visualization methods and bibliometric analysis. The results showed that the item with the most occurrences is